PELAKSANAAN PEMBERIAN KREDIT PADA KOPERASI SIMPAN PINJAM SAHABAT MITRA SEJATI CABANG AIR MOLEK DENGAN JAMINAN YANG DIJUAL DI BAWAH TANGAN - Silvya Pramunesa Bondes; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Conducting borrowing and borrowing activities to meet certain needs is already a natural thing in everyday life. In the case of Debitor Cooperative Savings and Loans Branch of Molec Air performing Default does not pay the credit and previously the Cooperative has tried to do the Calling Letter. Subsequently the Cooperative makes a sale under the hands of the Debtor's guarantee. Problems encountered are the Creditor selling the guarantee under the hand under the power of attorney at the beginning of the agreement contrary to the rules stipulated in the Instruction of the Minister of Home Affairs Number 14 of 1982 concerning the Prohibition on the Use of Absolute Power as the transfer of Land Rights. The purpose of writing this thesis, Firstly, knowing the way of giving problem loans with the sale of collateral under the hands, Secondly, knowing how to solve problem loans on Savings Partners Cooperative Mitra Sejati Air Molek Branch, and Legal Consequences if collateral is sold under the hand.The type of research used is descriptive sociological research. This research was conducted at the Savings and Loans Cooperative of Air Molek Branch in Indragiri Hulu Riau. Sedangan Populasi and Sampel is a whole party related to the problem under study. Sources of data used, primary data, secondary data and tertiary data, data collection techniques in this study by observation, interview and literature study.From the research and discussion to conclude there are three main things that can be concluded. First, the crediting of Cooperative Sahabat Mitra Sejati Branch of Molek Water is based on the regulation set by the Cooperative with 5c analysis (Character, Capacity, Capital, Condition, Collateral). Second, the Settlement in the event of Non-performing Credit in Cooperatives is carried out under the hands, if the guarantee with the power of attorney agreement at the beginning. Thirdly, the consequences of the law if done under the hands of such absolute Power, in accordance with the Absolute Prohibition of Attorney meant in the Instruction of the Minister of Home Affairs Number 14 of 1982 concerning the Prohibition on the Use of Absolute Power, it can be said null and void. Suggestion Writer, First, to the Customer, in order to have a cooperative attitude in completing the credit. Secondly, the Cooperative should not commit the contract under the hand with the Absolute Power at the beginning of the agreement.Keywords: Implementation-Credit-Agreement-Guarantee